2008
DOI: 10.1590/s1415-43662008000600006
|View full text |Cite
|
Sign up to set email alerts
|

Desenvolvimento de Heliconia psittacorum e Gladiolus hortulanus irrigados com águas residuárias tratadas

Abstract: RESUMOO objetivo primordial com este trabalho é avaliar o impacto do uso de águas residuárias domésticas tratadas (ART) no desenvolvimento de espécies ornamentais, razão por que se instalou o ensaio no município de Simões Filho, BA, em delineamento experimental de blocos casualizados, com parcelas subdivididas, cultivadas com Heliconia psittacorum e Gladiolus hortulanus e irrigadas por gotejamento com ART e com água de riacho; avaliaram-se o comprimento das hastes, número de botões florais (helicônia e gladíol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
2
17

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 6 publications
1
5
2
17
Order By: Relevance
“…Thus, growth rate may be reduced and the deficiency symptoms related to the already caused metabolic disorders may appear only later. On the other hand, the mean contents of P in the leaves in the present study were higher than the mean of 1.17 g kg -1 observed by Santos et al (2012), but lower than the range of 1.87 to 1.93 g kg -1 reported by Cerqueira et al (2008) and 1.77 g kg -1 obtained by Viégas et al (2014) for the cultivation of heliconias.…”
Section: Resultscontrasting
confidence: 83%
See 1 more Smart Citation
“…Thus, growth rate may be reduced and the deficiency symptoms related to the already caused metabolic disorders may appear only later. On the other hand, the mean contents of P in the leaves in the present study were higher than the mean of 1.17 g kg -1 observed by Santos et al (2012), but lower than the range of 1.87 to 1.93 g kg -1 reported by Cerqueira et al (2008) and 1.77 g kg -1 obtained by Viégas et al (2014) for the cultivation of heliconias.…”
Section: Resultscontrasting
confidence: 83%
“…The mean leaf K contents observed in the present study are between 18.23 and 27.1 g kg -1 , and are higher than the range of 17.4 to 18.7 g kg -1 observed by Santos et al (2012), the amplitude of 14.0 to 16.5 g kg -1 (Cerqueira et al, 2008) and the value of 2.59 g kg -1 (Viégas et al, 2014). The leaf K contents in this study are below the range of 35-45 g kg -1 reported by Atehortua (1997), although no visual symptom of deficiency was observed at the field.…”
Section: Bcontrasting
confidence: 59%
“…Para esta pesquisa, o aumento do nível de água residuária nos tratamentos levou a uma tendência de crescimento das variáveis estudadas em ambos os manejos de adubação. Já Cerqueira et al (2008), avaliando o impacto do uso de água residuária doméstica tratada e água de riacho no desenvolvimento das espécies ornamentais Heliconia psittacorum e Gladiolus hortulanus, não observaram diferença estatística entre os tipos de água utilizados.…”
Section: Discussionunclassified
“…O CHF em flores tropicais pode afetar diretamente a qualidade e o valor final do produto pois com inflorescências maiores é possível fazer arranjos mais robustos com um número menor de hastes (Arruda et al, 2008). Contudo, Cerqueira et al (2008) e Souza et al (2009) utilizando adubação semelhante e diferentes fontes de calcário encontraram comprimentos similares de hastes florais em "Golden Torch" mas não constataram diferenças no CHF. Os autores relatam que a baixa disponibilidade de nutrientes das fontes de silício utilizadas pode ter sido preponderante para que não houvesse diferença.…”
Section: Methodsunclassified